Analiza graficznej zasady kontrastu w Zawrocie głowy Alfreda Hitchcocka - Smaga, Agnieszka (Załącznik Kulturoznawczy, 2020)
The film was a purely visual event for Hitchcock. That is why the director enjoyed using the means of pictorial expression, such as contrasts in: scale – small and large; tone – light and dark, colors – complementary colors (red and green, yellow and blue), shape – round and sharp forms, direction – horizontal and vertical; planes – built-up areas and undeveloped, open and closed areas; textures – smooth and rough. Contrasts appeared within: single frame, shot, scene and sequence. The suggested graphic oppositions contributed to the phenomenon of suspense that Hitchcock was a master of. In this case, the suspension of the course of action was required through the collection of information and its synthesis, which was carried out with the use of visual contrasts, which led to cognitive oppositions. During the suspension of the course of events, the viewer was either curious about the further development of events or anticipated what might happen, but did khow it would happen. The viewer then felt a certain kind of tension. The analyzed image contrast was the source of this perceptual and then cognitive tension. It had to be strong enough to be actually effective. Then the image became visually attractive (1), thus immersive (2) and therefore persuasive (3). The sudden close-up of the face and its sudden distance away, the play of complementary colors, textures and space, all these phenomena caused the anticipated perception shock. Suspension – considered from the psychological level – also consisted of two contrasting states: fear and hope, which induced cognitive uncertainty. Both opposing mental states were built, among others, through the contrasts of images: scale, tone, color, texture (also sonic and kinetic dissonances).